Deciding to distrust - Iris Bohnet; Stephan Meier (Federal Reserve Bank of Boston, 2005)
We employ experiments to illustrate one factor contributing to the lack of distrust in the recent corporate scandals: Trust rather than no trust was the default. People are more trusting when the default is full trust than when it is no trust. We introduce a new game, the distrust game (DTG), where the default is full trust and find that in it, trust levels are higher than in the Berg, Dickhaut, and McCabe (1995) trust game (TG), where the default is no trust. At the same time, trustworthiness levels are lower in the DTG than in the TG. Agents (second movers) punish distrust more in the DTG than the lack of trust in the TG, but principals (first movers) do not correctly anticipate this. The distrust game produces more efficient outcomes than the trust game but also more inequality: Principals end up much worse than their agents in the DTG.
Keywords: C72; C91; 330; trust; reciprocity; reference points; behavioral economics; experimental economics; Vertrauen; Spieltheorie; Test; Verhalten